The knowledge, training, and willingness of first year students in Xuzhou, China to perform bystander cardiopulmonary resuscitation: a cross-sectional study - Qin, Zhaohui; Zheng, Shuyao; Liu, Chenxu; Ren, Yuxin; Wang, Ran; Zhang, Sitian; Gu, Xiao; Li, Yichen; Yan, Xianliang; Xu, Tie (Frontiers in Public Health, 2024)
Background: Bystander Cardiopulmonary Resuscitation (CPR) can significantly improve the rate of return of spontaneous circulation in patients with cardiac arrest. Since first year students with no specific academic background are energetic and quick to learn, many Chinese schools offer first-aid training course including CPR to them before they start school. However, data on CPR knowledge, training, and willingness among first year students are lacking in most regions of China, which makes the effectiveness of CPR training unknown..To evaluate first year students' knowledge level, training experience and rescue willingness for CPR of first year students in Xuzhou, and to analyse the influencing factors of CPR knowledge level and rescue willingness of first year students in Xuzhou.Participations: A total of 9887 first year students from three universities in Xuzhou city were selected by multi-stage random cluster sampling method.Methods: A self-designed five-part structured questionnaire was used to investigate the knowledge, training and willingness of CPR among first year students. Independent sample t-test,  2 -test and Logistic regression were used for data analysis.The average score of CPR knowledge was 2.44 ( 1.60), 99.13% of the respondents were willing to participate in CPR training, and 66.25% had received CPR training. Respondents with rural household registration, relatives who had suffered from serious diseases, relatives engaged in the medical profession, good self-rated quality of life, CPR training, and willing to CPR training had higher CPR knowledge levels. 76.77% of the respondents were willing to perform bystander CPR. Women, those who had received CPR training, and those who were willing to receive CPR training were more willing to help patients with sudden cardiac arrest. Lack of first aid knowledge and skills (82.61%) was the biggest obstacle hindering respondents from performing rescue.: Most of the first-year students of Xuzhou University in China have CPR training experience and have a strong willingness to train. Most are willing to perform bystander CPR, but have a low knowledge level. Colleges and universities can adopt diversified training methods, make plans for regular CPR retraining and other strategies to improve the quality and effect of CPR training for college students.